Route optimization scheme for nested mobile networks based on extending neighbor discovery protocol - Xing YIN; Guo-xin WU; Yong-qiang DONG; San-feng ZHANG (Tongxin xuebao)
Nested mobile networks face the challenge of route optimization (RO) even it can expend the scope of communications.The existing RO approaches have the limitation of low performance and difficulty of deployment.A nested mobile networks route optimization (NMNRO) scheme is proposed by extending the neighbor discovery protocol，in which foreign prefixes in nested networks are advertised，and the destination caches of access routers and the routing tables of mobile routers are updated accordingly.After that，a correspondent registration is performed in order to implement RO.Performance analysis shows that NMNRO provides an overall RO solution with lower overhead，better compatibility，and higher deployability.Simulation results demonstrate that NMNRO has lower handover delay and higher goodput than other schemes，and the performance advantage appears more significant with the increase of nesting level.